Indigenous research methodologies - Chilisa, Bagele (New Delhi Sage, 2020)
"Author Bagele Chilisa updates her groundbreaking textbook to give a new generation of scholars a crucial foundation in indigenous methods, methodologies, and epistemologies. Addressing the increasing emphasis in the classroom and in the field to sensitize researchers and students to diverse perspectives - especially those of women, minority groups, former colonized societies, indigenous people, historically oppressed communities, and people with disabilities, the second edition of Indigenous Research Methodologies situates research in a larger, historical, cultural, and global context to make visible the specific methodologies that are commensurate with the transformative paradigm of social science research"--
Keywords: Indigenous peoples -- Research -- Methodology; Postcolonialism -- Research -- Methodology